Prevalence of intestinal parasitic infection and its associated factors among primary school students in Ethiopia: A systematic review and meta-analysis. - Moges Agazhe Assemie; Daniel Shitu Getahun; Yidersail Hune; Pammla Petrucka; Ayele Mamo Abebe; Animut Takele Telayneh; Mekdes Marew Ambaw; Daniel Bekele Ketema; Temesgen Getaneh; Belayneh Mengist; Muluneh Alene; Samuel Derbie Habtegiorgis (Public Library of Science (PLoS), 2021)
Introduction Intestinal parasitic infection are a major public health concern affecting both children and adolescents in Ethiopia. The aim of this systematic review and meta-analysis was to determine pooled prevalence and associated factors of intestinal parasitic infection in this target group. Method We systematically retrieved available articles on the prevalence of intestinal parasitic infection following database searches using PubMed, Scopus, Cochrane Library, and Science Direct between March 1 and May 27, 2020. Two authors independently extracted all relevant data using a standardized Microsoft Excel data extraction form. Heterogeneity among included studies was assessed with the Higgins I2 tests. The pooled estimates and associated factors were assessed with a random-effects model using Stata/se Version 14. Result We retrieved 30 eligible articles with a pooled sample size of 14,445 primary school children with response rate of 97.8%. Entamoeba spp (16.11%), Ascaris lumbricoides (13.98%), hookworm (12.51%) and Giardia lamblia (9.98%) are the top causes of intestinal parasitic infection among primary school children in Ethiopia. The pooled prevalence for at least one intestinal parasitic infection was 46.09 (95% CI: 38.50, 53.68). Heterogeneity was assessed by doing subgroup analysis by study province/region. Thus, the highest prevalence of 66.6% (95% CI: 55.5, 77.7) occurred in Tigray region, which was followed by Southern Nations, Nationalities, and Peoples' Region at 50.8% (95% CI: 33.1, 68.5). No latrine availability (OR = 4.39: 2.50,7.73), no fingernail hygiene (OR = 2.37: 1.67, 3.35), open defecation (OR = 1.67:1.64,4.36), no formal maternal education (OR = 2.02: 1.18,3.47), rural residence (OR = 1.88: 1.46, 2.41), no habit of wearing shoes (OR = 2.66: 1.79, 3.96), non-pipe source of drinking water (OR = 1.99: 1.42,2.76), no regular hand washing practices (OR = 3.45:1.85,6.47), and no habit of washing fruits and vegetables (OR = 1.59:1.01,2.49) were associated with parasitic infection. Conclusions The prevalence of intestinal parasitic infection was high (46%). Attention should be given to promoting personal hygiene, latrine utilization, wearing shoes, avoiding eating raw food, creating awareness for those mothers who lack formal education. Moreover, future research ideally will expand on the topic by conducting research in regions which have no prior research.